Implications of More Precise Information for Technological Development and Welfare - Eckwert, Bernhard (IMF Working Papers; Working Paper, 2007)
This paper analyzes the dynamic interactions between the precision of information, technological development, and welfare within an overlapping generations model. More precise information about idiosyncratic production shocks has ambiguous effects on technological progress and welfare, which depend critically on the risk sharing capacity of the economy's financial system. For example, we show that with efficient risk sharing more precise information adversely affects the equilibrium risk allocation and creates a negative uncertainty-related welfare effect, at the same time as it accelerates technological progress and increases R and D investment.